16O-rich anhydrous silicates in CI chondrites: Implications for the nature and dynamics of dust in the solar accretion disk. (1st September 2022) - Morin, Gatien L.F.; Marrocchi, Yves; Villeneuve, Johan; Jacquet, Emmanuel
Abstract: CI chondrites have nonvolatile chemical compositions closely resembling that of the Sun's photosphere and are thus considered to have the most primitive compositions of all known solar system materials. They have, however, experienced pervasive parent-body alteration processes that transformed their primary constituents, obscuring the nature and origin of primordial CI dust. We used in-situ quantitative microprobe and secondary ion mass spectrometry techniques to characterize the chemistry and oxygen isotopic compositions of anhydrous silicates in two sections of the CI chondrites Ivuna and Alais, which contain higher abundances of those than other CI samples. These silicates are Mg-rich olivine and low-Ca pyroxene crystals mostly occurring as aggregates within sub-mm Fe-rich clasts. Our data reveal mass-independent oxygen isotopic variations with Δ 17 O values ranging from −23.63 to −0.57‰, representing the first evidence of extremely 16 O-rich (Δ 17 O < −20‰) olivine and pyroxene grains in CI chondrites. Two of these olivines are characterized by MnO/FeO ∼ 1, typical of low-iron, Mn-enriched silicates commonly observed in amoeboid olivine aggregates. Other anhydrous silicate grains have Δ 17 O values ranging from −6 to 0‰, probably representing chondrule fragments. Combined, these results indicate that chondrule and refractory inclusion material were incorporated into the CI parent body(ies). This conclusion is consistent with recent models showing that refractory inclusions could have formed and/or been transported at larger heliocentric distances than previously thought during the concomitant injection of material from the molecular cloud and outward extension of the disk by viscous spreading. The CI chondrules are presumably of local origin, with their isotopic systematics suggesting an affinity with the CR clan.